Major bleeding risk prediction using Chronic Kidney Disease Epidemiology Collaboration and Modification of Diet in Renal Disease equations in acute coronary syndrome - Flores-Blanco, Pedro J.; López-Cuenca, Ángel; Januzzi, James L.; Marín, Francisco; Sánchez-Martínez, Marianela; Quintana-Giner, Miriam; Romero-Aniorte, Ana I.; Valdés, Mariano; Manzano-Fernández, Sergio (European journal of clinical investigation, 2015)
Background Chronic Kidney Disease Epidemiology Collaboration (CKD‐EPI) equations estimate glomerular filtration rate more accurately than the Modification of Diet in Renal Disease (MDRD) Study equation. Our aim was to evaluate whether CKD‐EPI equations based on serum creatinine and/or cystatin C (CysC) predict risk for major bleeding (MB) more accurately than the MDRD Study equation in patients with non‐ST‐segment elevation acute coronary syndromes (ACS). Materials and methods Three hundred and fifty consecutive subjects with non‐ST‐segment elevation ACS (68 ± 12 years, 70% male) were studied. Glomerular filtration rate was estimated using the CKD‐EPI and MDRD Study equations. The primary endpoint was the occurrence of MB during the follow‐up, which was defined according to the Bleeding Academic Research Consortium Definition criteria as bleeding types 3–5. Results During the median follow‐up of 589 days (interquartile range, 390–986), 27 patients had MB (0·04% events per person year). Patients with MB had worse kidney function parameters, regardless of the estimating equation used (P < 0·001). After multivariate Cox regression adjustment, both CysC‐based CKD‐EPI equations were independent predictors of MB (CKD‐EPIcreatinine‐cystatin C per mL/min/1·73 m2, HR = 0·973 (95%CI 0·955–0·991; P = 0·003) and CKD‐EPIcystatin C per mL/min/1·73 m2, HR = 0·976 (95%CI 0·976–0·992; P = 0·003), while the CKD‐EPIcreatinine and MDRD equations did not achieve statistical significance. Both CKD‐EPIcreatine‐cystatin C and CKD‐EPIcystatin C were associated with a significant improvement in MB risk reclassification. Conclusions In this cohort of non‐ST‐segment elevation ACS patients with relatively preserved renal function, both CysC‐based CKD‐EPI equations improved ability to predict risk for MB and were superior to other equations for this application.